2021
DOI: 10.1371/journal.pone.0249949
|View full text |Cite
|
Sign up to set email alerts
|

Experimental in-vitro investigation on Epi-Off-Crosslinking on porcine corneas

Abstract: Aim To evaluate quantitatively the effects of the Epi-Off-CXL irradiance dose on the stromal stiffening of pig corneas. Setting Laboratory of Biological structures (LaBS), Politecnico di Milano, Milano, Italy. Methods Inflation tests have been carried on 90 excised and de-epithelized pig corneas, monitoring the change of configuration of the corneal dome at specific pressures. Test have been carried out twice on each cornea, once before and once after Epi-Off-CXL performed at a constant irradiance of 9 mW/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 33 publications
1
24
1
Order By: Relevance
“…Interestingly, the theoretical model, supported by experimental data, revealed that the effect of CXL depends more on the duration of the irradiation than on the overall applied UV-A intensity (fluence). A recent experimental study on pressurized porcine corneas tested the stiffening effect of different irradiation time (2.5, 5, 10, 15, 20 min) of de-epithelialized corneas [10]. Results demonstrated that the duration of the irradiation has a marked effect on stromal stiffening, in agreement with the previous theoretical model.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, the theoretical model, supported by experimental data, revealed that the effect of CXL depends more on the duration of the irradiation than on the overall applied UV-A intensity (fluence). A recent experimental study on pressurized porcine corneas tested the stiffening effect of different irradiation time (2.5, 5, 10, 15, 20 min) of de-epithelialized corneas [10]. Results demonstrated that the duration of the irradiation has a marked effect on stromal stiffening, in agreement with the previous theoretical model.…”
Section: Introductionsupporting
confidence: 83%
“…It is well established that the stiffening effect due to CXL treatment is highly dependent on the duration of treatment and that the stiffness distribution within the cross-section is inhomogeneous. A recent numerical study attempted to provide a relationship between the stiffness depth of penetration and the treatment duration [13], by making use of the experimental data presented in [10]. To limit the introduction of arbitrary fitting coefficients, the through-thickness CXL stiffening of the cornea was assumed as piece-wise-constant.…”
Section: Introductionmentioning
confidence: 99%
“…The finite element analysis provided at increasing irradiation doses proved that the increase in the cross-link density at a comparatively high value of irradiation dose could help improve the material strength, thus increasing the fluence not only provides an increased depth in the demarcation lines, but an increased cornea resistance that is crucial in Epi-On treatments. These clinical and experimental observations confirmed that the way to go for Epi-On CXL treatments is to find a balance between the riboflavin concentration and higher fluence between 8.1 and 10.8 J/cm 2 [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, post-CXL tests are characterized by low to moderate dispersion around the average. 26 The discrepancy may be attributed to the differences in irradiance of VL in the KeraVio procedure (0.31 mW/cm 2 for 4.8 hours). Long-term irradiation of VL on the cornea can induce degradation over time in an ex vivo porcine eye model.…”
Section: Discussionmentioning
confidence: 99%